The digital technological revolution: Challenges for the working class, trade union organizations, and States in Latin America - Barillas Girón, Byron Renato (2026)
This paper aims, on one hand, to provide a conceptual framework for various aspects and relationships that are often hidden within the dynamics of new digital technologies, and, more importantly, to offer a critical perspective on the so-called Industrial Revolution 4.0 and 5.0, characterized by the rapid advancement of digital technologies, seeking to emphasize both their positive and negative impacts, as well as the challenges they pose for economies and productive processes, highlighting the possibilities alongside the risks or threats present in the labor sphere.